Archaic Period Shell Middens, Sea-Level Fluctuation, and Seasonality: Archaeology along the Northern Gulf of California Littoral, Sonora, Mexico. Issue 4 (20th October 2012) - Foster, Michael S.; Mitchell, Douglas R.; Huckleberry, Gary; Dettman, David; Adams, Karen R.
Abstract: Five recent radiocarbon assays on wood charcoal within archaeological sites from the Puerto Peñasco area, Sonora, Mexico indicate use of the marine resources of the northern Gulf of California area during the Middle Archaic through the Late Archaic periods, ca. 3800 B.C.–A.D. 100. The archaeological shell middens of the region are generally thought of as remains associated with Ceramic period Hohokam marine shell collecting forays with there being little consideration given to the likelihood of an Archaic period component being present. The importance of these age estimates is that they are derived from carbonized botanical remains rather than shell. Because of considerable variability in the carbon reservoir effect, age estimates derived from marine shell from the northern Gulf of California have limited reliability. The seasonality of collection is also considered through a preliminary study of stable oxygen isotope ratios in two shell samples. The results suggests that these shellfish were collected in the late fall, winter, and perhaps very early spring.